Kesantunan Berbahasa dalam Ceramah Gus Miftah: Suatu Kajian Pragmatik - Suraia Revameilawati; Ary Setyadi; Riris Tiani (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
[Principle Politeness in Gus Miftah Lectures (Study of Pragmatic)] This study aims to explain the form of language politeness, and the determinants of language politeness in Gus Miftah's lecture. The data in the study are Gus Miftah's speeches in four lecture shows that fall into the category according to the research objectives. The data collection method used the listening method, with free listening and speaking techniques and note-taking techniques. The results of the analysis are presented using informal methods. The results of the study found 5 compliance with the principle of politeness and 12 violations of the principle of politeness. Violations of the principle of politeness are found more than the application of the principle of politeness, because speakers make a lot of jokes to lighten the atmosphere, but the jokes made by speakers seem less polite and have the potential to hurt some parties. The linguistic factors that determine politeness in language in this data are the use of diction which includes the use of various languages, the use of harsh words, the use of swear words, and the use of language styles, namely similes. While the non-linguistic factors that determine politeness are the context of the communication situation, and sociocultural institutions.